A Cross-National Analysis of State Institutional Authority Disputes - Hafidz, Jawade (Hasanuddin Law Review, 2025)
The distribution of authority among state institutions is a fundamental component of any governmental framework, as it helps prevent jurisdictional overlaps that could lead to institutional conflicts. When such conflicts over authority do occur, it becomes imperative to have a mechanism in place for their resolution. This study is designed to explore and analyze the comparative regulatory structures for resolving authority disputes among state institutions, as outlined by the legislation in Indonesia, the United States, Germany, and Canada. Furthermore, the research aims to identify the characteristics of disputes concerning state institutional authority and suggest optimal regulatory solutions for their resolution. Utilizing a qualitative and descriptive research approach, this study will clarify the regulatory frameworks for dispute resolution among state institutions, as defined by the current legislation in each country. Each framework is characterized by unique institutions and methods for resolving disputes. The findings reveal that the German Constitutional Court holds the most comprehensive jurisdiction, covering all state institutions in Germany, both at the central and regional levels. In terms of procedural aspects, the legal framework for resolving authority disputes in Germany is more detailed than those in Indonesia, the United States, or Canada, thereby promoting greater transparency and accountability in the dispute resolution process in Germany.